Anticoagulants Resumption after Warfarin-Related Intracerebral Haemorrhage: The Multicenter Study on Cerebral Hemorrhage in Italy (MUCH-Italy) - Poli, Loris; Grassi, Mario; Zedde, Marialuisa; Marcheselli, Simona; Silvestrelli, Giorgio; Sessa, Maria; Zini, Andrea; Paciaroni, Maurizio; Azzini, Cristiano; Gamba, Massimo; Toriello, Antonella; Tassi, Rossana; Giorli, Elisa; Calabrò, Rocco Salvatore; Ritelli, Marco; De Vito, Alessandro; Pugliese, Nicola; Martini, Giuseppe; Lanari, Alessia; Lodigiani, Corrado; Padroni, Marina; De Giuli, Valeria; Caria, Filomena; Morotti, Andrea; Costa, Paolo; Strambo, Davide; Corato, Manuel; Pascarella, Rosario; Del Sette, Massimo; Malferrari, Giovanni; Colombi, Marina; Padovani, Alessandro; Pezzini, Alessandro; on behalf of the Multicenter Study on Cerebral Hemorrhage in Italy (MUCH-Italy) Investigators (Thrombosis and Haemostasis, 2018)
Whether to resume antithrombotic treatment after oral anticoagulant–related intracerebral haemorrhage (OAC-ICH) is debatable. In this study, we aimed at investigating long-term outcome associated with OAC resumption after warfarin-related ICH, in comparison with secondary prevention strategies with platelet inhibitors or antithrombotic discontinuation. Participants were patients who sustained an incident ICH during warfarin treatment (2002–2014) included in the Multicenter Study on Cerebral Hemorrhage in Italy. Primary end-point was a composite of ischemic stroke/systemic embolism (SE) and all-cause mortality. Secondary end-points were ischemic stroke/SE, all-cause mortality and major recurrent bleeding. We computed individual propensity score (PS) as the probability that a patient resumes OACs or other agents given his pre-treatment variables, and performed Cox multivariable analysis using Inverse Probability of Treatment Weighting (IPTW) procedure. A total of 244 patients qualified for the analysis. Unlike antiplatelet agents, OAC resumption was associated with a lower rate of the primary end-point (weighted hazard ratio [HR], 0.21; 95% confidence interval [CI], 0.09–0.45), as well as of overall mortality (weighted HR, 0.17; 95% CI, 0.06–0.45) and ischemic stroke/SE (weighted HR, 0.19; 95% CI, 0.06–0.60) with no significant increase of major bleeding in comparison with patients receiving no antithrombotics. In the subgroup of patients with atrial fibrillation, OACs resumption was also associated with a reduction of the primary end-point (weighted HR, 0.22; 95% CI, 0.09–0.54), and the secondary end-point ischemic stroke/SE (weighted HR, 0.09; 95% CI, 0.02–0.40). In conclusion, in patients who have an ICH while receiving warfarin, resuming anticoagulation results in a favorable trade-off between bleeding susceptibility and thromboembolic risk.
Keywords: stroke; haemorrhage; anticoagulants